TREATMENT OF THE CHRONIC PAIN SYNDROME AT THE INCURABLE ONCOLOGICAL PATIENTS - L. N. Kudryashovа; A. A. Kudryashov; O. M. Petrovа (Креативная хирургия и онкология, 2017)
The material  is presented in article about the principles of treatment of a chronic pain syndrome at oncological  patients on the  example  of experience of office of the  palliative help of the Republican clinical Oncology  Dispensary of Ufa. The office structure, methods and  schemes of  treatment of  pain at patients with  generalized forms  of  a cancer  are  in detail stated.